Firm Credit Experience and Perceptions of Lending Policy: Business Survey Evidence from Austria - Christa Hainz; Jarko Fidrmuc; Werner Hölzl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Bank lending has been a major concern since the financial crisis. We study the effect of a firm's own credit market experience on its perceived bank lending policy using the Austrian Business Climate Survey between 2011 and 2014 and. Our results show that firms' perceptions of aggregate lending policy depend on their individual credit market experience. Only if they get the loan at the expected terms, firms are more likely to perceive the banks' lending policy positively. Moreover, firms are more likely to update their perceptions during the period in which they need a loan. Our results are in line with theories on sticky information, rational inattention and pessimism bias when forming perceptions.
Keywords: G21; E51; D03; 330